Eschatological Aesthesis in Orthodox Hymnography and Iconography: Religious Consciousness in Medieval Rus - Nadezhda Z. Gayevskaya (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine the formation of eschatological aesthesis in Orthodox hymnography and iconography in medieval Rus’ as a constitutive mode of religious consciousness. The study is important because previous scholarship on Orthodox eschatology has tended to emphasize doctrine, symbolism, or iconographic content without adequately explaining how eschatological meaning is organized through perception, affect, and liturgical experience. This research employs a qualitative, document-based design with a phenomenological-hermeneutic approach. Data were collected through close reading and document analysis of selected hymnographic and liturgical texts, Old Russian hagiographical narratives, and a representative iconographic form of the Last Judgment. The findings show that eschatological motifs such as resurrection, judgment, divine light, repentance, and kenosis are aesthetically structured through rhythm, repetition, metaphor, and symbolic contrast in the selected texts. The study also finds that eschatological meaning is intensified through the integration of visual, auditory, bodily, and symbolic elements within liturgical practice, while temporal structures of memory, anticipation, and calendrical repetition stabilize this experience into a durable religious habitus. These findings contribute to religious studies by showing that eschatology in medieval Orthodox culture functioned not merely as doctrine, but as a multisensory and temporal mode of consciousness formation. The originality of this study lies in its formulation of eschatological aesthesis as a perceptual and symbolic synthesis that connects hymnography, iconography, and liturgical temporality within a single analytical framework.